Patterns Of Character Education In Islamic Boarding Schools In Anticipating Radicalism In The Industrial Revolution Era 4.0 - Khalid Ramdhani; Kasja Eki Waluyo; Acep Nurlaeli (At-Tarbiyat, 2023)
Islamic boarding schools, as Islamic educational institutions that pay attention to the field of community empowerment, must be prepared to face the era of the industrial revolution 4.0 in producing students who have good character with extensive religious knowledge so that they avoid the traps of radicalism that are spread on the broader community and also on social media even when The government is also aggressive in anticipating and eradicating radical ideas. The purpose of this study is to describe how the management of the Baitul Burhan Islamic boarding school in building character and anticipating radicalism in the industrial era 4.0 has damaged the good image of Islam as a religion that is rahmatan lil alamin. This study used a descriptive qualitative approach with the method used, namely the case study method. This research was conducted at the Baitul Burhan Islamic Boarding School Lemahduhur Tempuran Karawang. The study results show that in carrying out their work, Islamic boarding schools in the last few decades have often been the target of suspicion by many elements of society and law enforcement; Islamic boarding schools are places to educate radicalism and terrorism. Based on the study's results, Islamic boarding schools were not found as a source of radicalism and terrorism. Even Islamic boarding schools play a role in preventing radicalism and terrorism with a pattern of character education.